2007
DOI: 10.17221/2338-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the application of bioplexes of zinc, copper and manganese on milk quality and composition of milk and colostrum and some indices of the blood metabolic profile of cows

Abstract: AbstrACt:The object of an experiment was inorganic and organic forms of zinc, copper and manganese applied in mineral mixtures to dairy cows. The experiment was carried out on 90 cows with average milk yield for previous lactation of about 9 500 kg milk. The cows received mineral mixtures containing inorganic or organic forms of zinc, copper and manganese for 6 weeks before calving and during the first three months of lactation. The application of microelements as bioplexes in amounts covering 30% of daily req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 4 publications
2
14
0
10
Order By: Relevance
“…There were no effects of treatment on plasma concentrations of GL, NEFA, β-hydroxybutyrate, TC, CHDL, TP, albumin, urea, BUN, β-hydroxybutyrate, alkaline phosphatase or β-hydroxybutyrate, either pre-partum or during lactation (Table 2). Similarly, Kinal et al (2007a) did not observe effect of supplementation of organic Zn, Cu or Mn from six weeks pre partum to three months of lactation on concentrations of urea and GL. However, a time effect was observed in this study for all variables during both periods, except for β-hydroxybutyrate pre-partum and concentrations of β-hydroxybutyrate and β-hydroxybutyrate during the first 80 d of lactation.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…There were no effects of treatment on plasma concentrations of GL, NEFA, β-hydroxybutyrate, TC, CHDL, TP, albumin, urea, BUN, β-hydroxybutyrate, alkaline phosphatase or β-hydroxybutyrate, either pre-partum or during lactation (Table 2). Similarly, Kinal et al (2007a) did not observe effect of supplementation of organic Zn, Cu or Mn from six weeks pre partum to three months of lactation on concentrations of urea and GL. However, a time effect was observed in this study for all variables during both periods, except for β-hydroxybutyrate pre-partum and concentrations of β-hydroxybutyrate and β-hydroxybutyrate during the first 80 d of lactation.…”
Section: Resultsmentioning
confidence: 69%
“…Other authors (Spears et al, 2004;Kinal et al, 2007b) also reported an increase in Zn in plasma in cattle fed organic or inorganic Zn. Similarly, Kinal et al (2007a) reported an increase in plasma Cu concentration of dairy cows fed organic sources of Zn, Cu and Mn compared with cows fed these minerals as sulphate.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Regarding animal products, no difference in copper levels in eggs were observed between hens fed diets supplemented with copper sulphate or chelated amino acid hydrate at levels that did not exceed the maximum authorised total element level (Mabe et al, 2003) or with levels highly exceeding it (Idowu et al, 2006). Data from one study carried out with dairy cows (total dietary copper 13.8 mg/kg) did not show any difference in milk copper levels depending on copper source (Kinal et al, 2007).…”
Section: Copper Deposition In Tissues and Products Of Animal Originmentioning
confidence: 84%
“…Ashmead et al (2004) recorded that amino acid chelates (AACs) were more bioavailable than inorganic minerals (IOMs). Kinal et al (2007) Mallaki et al (2015) reported that dry matter intake were higher for the lambs fed the diet supplemented with ZnP. Feed conversion ratio was significantly (P < 0.05) higher in the ZnP group compared to the control and ZnS groups.…”
Section: Body Weight Gainmentioning
confidence: 95%